2018
DOI: 10.1172/jci120555
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive T effector memory differentiation mirrors β cell function in type 1 diabetes

Abstract: In type 1 diabetes, cytotoxic CD8+ T cells with specificity for β cell autoantigens are found in the pancreatic islets, where they are implicated in the destruction of insulin-secreting β cells. In contrast, the disease relevance of β cell-reactive CD8+ T cells that are detectable in the circulation, and their relationship to β cell function, are not known. Here, we tracked multiple, circulating β cell-reactive CD8+ T cell subsets and measured β cell function longitudinally for 2 years, starting immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 62 publications
1
51
0
Order By: Relevance
“…We found that the comprehensively defined islet-specific phenotypes, though variable across individuals, did not significantly differ by disease status and, indeed, were also present in HCs. Using established markers of CD8 + T cell differentiation, Yeo et al described a positive correlation between changes in C-peptide and changes in effector memory CD57 + β cell-specific CD8 + T cells among young individuals who were newly diagnosed with T1D, implicating antigen load as a driver of differentiation and peripheral migration of this T cell subset (53). However, the relationship of autoreactive CD8 + T cell function and rate of progression in established T1D remains relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the comprehensively defined islet-specific phenotypes, though variable across individuals, did not significantly differ by disease status and, indeed, were also present in HCs. Using established markers of CD8 + T cell differentiation, Yeo et al described a positive correlation between changes in C-peptide and changes in effector memory CD57 + β cell-specific CD8 + T cells among young individuals who were newly diagnosed with T1D, implicating antigen load as a driver of differentiation and peripheral migration of this T cell subset (53). However, the relationship of autoreactive CD8 + T cell function and rate of progression in established T1D remains relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…While much effort has been focused on immunological differences between T1D patients and healthy controls, or with transitions between stages of T1D (52,53), little information is available about associations between immunological features and rates of C-peptide loss following diagnosis. One notable exception is the recent discovery of a subpopulation of autoreactive CD8 + effector memory T cells in the blood whose levels parallel β cell function, suggesting that these cells are either engaged in or tracking the autoimmune response (54). In addition, using a serum-induced expression assay, Cabrera et al (55) found that an index of immune inflammatory state predicted the rate of C-peptide loss in the first 2 years after diagnosis in a limited set of placebo-treated subjects; this relationship was ablated by CTLA4Ig therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Those memory cells that are formed are defective in pathogen recall responses [4]. Memory cells are the most prone to making proinflammatory cytokines, and memory or memory-like cells can underlie autoimmunity, even in cases of persistent selfantigen exposure [5][6][7]. These findings, and the strong associations between human polymorphisms in binding sites for Oct1 and predisposition for autoimmune disease including MS [11][12][13][14], suggested a possible role for Oct1 in promoting MS.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, CD4 + T cells lacking Oct1 are completely defective in memory recall responses. Memory T cells are highly prone to making proinflammatory cytokines, and memory or memory-like cells can underlie autoimmunity (including T1D), even in cases of persistent selfantigen exposure [5][6][7]. In vitro, Oct1 and its cofactor OCA-B coordinately control a large cohort of critical direct target genes in CD4 + lymphocytes, including Il2, Il21, Stat5a, Ifng, Tbx21 (Tbet), Csf2 (Gmcsf ), Tnfrsf4 (Ox40), Icos, and Ctla4 [4].…”
Section: Introductionmentioning
confidence: 99%